The psychological climate of the football players in Baghdad governorate clubs for the elite league and its relation with the results - Hazza, Abdullah (Journal of Physical Education, 2012)
The study aims at getting knowledge of the psychological level of the football players in Baghdad governorate elite clubs and its relation with the results in order to get an idea of which line is better of the game lines. The researcher has adopted the descriptive method to achieve the goal of the study .The sample of the study included(219)football players representing the following clubs (Zawra', ALJawiyeh, Talabah, Baghdad, sinaa', industry, Karkh, refinery and Hasaneen), from the research society comprised of (36)clubs taking part in the competition of football of the Iraqi elite tournament for the football season of 2010-2011.The researcher adopted the psychological measurement designed by Mohammed Hasan Alawi from Egypt which contains (20)items or descriptive and(20)opposed adjectives. The research reached numbers of deductions ,its most important deduction is that the psychological climate level was in the medium average and the mid-line is the best of all other lines as fares the psychological level is concerned and there differences in the psychological level among clubs and there is appositive relation between the psychological level and the results in football competitions of the sample of study .